"Why Is This So Hard?" A Review of Detection of Malingered ADHD in College Students. (April 2014) - Musso, Mandi W.; Gouvier, Wm. Drew
Objective: The purpose of this article is to review studies that have investigated malingered ADHD in college students and offer recommendations for assessing effort in clinical evaluations of ADHD in college students.Method: This article identified and summarized nineteen peer-reviewed, empirical studies published between 2002 and 2011 that investigated malingered ADHD in college students.Results: Few of the measures examined proved useful for detecting malingered ADHD. Most self-report questionnaires were not sensitive to malingering. While there is some variability in the usefulness of neuropsychological test failure, profiles between malingerers and individuals with ADHD are too similar to confidently detect malingered ADHD. Failure of three or more symptom validity tests proved most useful at detecting malingered ADHD.Conclusion: This review suggests that there is substantial need for measures designed specifically for detecting malingered ADHD simulators are able to produce plausible profiles on most tools used to diagnose ADHD.